Em busca de uma metodologia de análise documentária para as crônicas jornalísticas de Carlos Drummond de Andrade - Bastos, Dilza Ramos (2008)
The impact of new technologies on the processes of scientific communication has been generating new needs of investigation on the documental processing. In the research field of Literature and History, the information systems do not meet the needs of the increasing and more specific demand. The chronicle has great importance for research under several aspects, also for its thematic. However, its analysis can be a complex matter, because it s not possible to propose a textual structure for the chronicle, which demands an integral documentary reading. The dissertation presents, starting from literature revision, proposes an investigation of the nature of chronicles and the documentary analysis in its constituent phases. On the empirical field, the information representation in the documental processing of Carlos Drummond de Andrade s chronicles collection, published in the Jornal do Brasil, made in an unit of specialized information, will be analyzed. In this unit of information, specialists in literature and information professionals have created gradually some procedures with purpose of facilitating the analysis and the record of the resultant data. Thus, theoretical and methodological fundamentation is sought for the treatment of journalistic chronicles, in order to improve its documentary analysis and the assistance to current users, as well as for future researchers.